An ELF-based comparative analysis of teachers’ attitudes, classroom practices and materials in public and private schools in Portugal - Guerra, Luis (2019)
The concept of globalization is usually understood as a series of processes, which affect the world’s environment, economics, business, and socio-cultural resources. More specifically, it influences the way societies exchange goods, capital and knowledge. As a result, people’s actions, practices, beliefs and life styles are woven into a web of novel social relationships and the language that has become the preferred tool to increase this global interconnection is beyond doubt English. Inevitably, the leading role of English as a language of international communication calls for significant pedagogical changes in the approaches, mindsets and procedures, which have so far been dominant in the language classroom. Accordingly, this chapter aims to draw attention to some of these shifts at the same time identifying prospective differences between teachers’ attitudes and practices in public or private schools. To accomplish this, firstly, it will provide a brief introduction to the concepts of English as a Lingua Franca (ELF), English as an International Language (EIL) and World Englishes (WE), and then it will explain some of their pedagogical implications. Following that, it will examine two relevant theoretical frameworks for ELF/EIL-aware teacher education programs. Afterward, this chapter will analyze the results of a study that intended to identify ELF-aware teaching practices in Portugal. Next, it will present the findings of two further illustrative case studies (interviews) on teachers’ attitudes toward implementing ELF-based activities in public and private schools in Portugal. Finally, the chapter will provide some concluding remarks.